Linking gold mineralization to regional-scale drivers of mineral systems using in situ U–Pb geochronology and pyrite LA-ICP-MS element mapping - Fielding, Imogen O.H.; Johnson, Simon P.; Meffre, Sebastien; Zi, Jianwei; Sheppard, Stephen; Large, Ross R.; Rasmussen, Birger (Di xue qian yuan., 2019)
Proterozoic orogens commonly host a range of hydrothermal ores that form in diverse tectonic settings at different times. However, the link between mineralization and the regional-scale tectonothermal evolution of orogens is usually not well understood, especially in areas subject to multiple hydrothermal events. Regional-scale drivers for mineral systems vary between the different classes of hydrothermal ore, but all involve an energy source and a fluid pathway to focus mineralizing fluids into the upper crust. The Mount Olympus gold deposit in the Proterozoic Capricorn Orogen of Western Australia, was regarded as an orogenic gold deposit that formed at ca. 1738 Ma during the assembly of Proterozoic Australia. However, the trace element chemistry of the pyrite crystals closely resembles those of the Carlin deposits of Nevada, with rims that display solid solution gold accompanied by elevated As, Cu, Sb, Hg, and Tl, surrounding gold-poor cores. New SHRIMP U–Pb dating of xenotime intergrown with auriferous pyrite and ore-stage alteration minerals provided a weighted mean 207Pb*/206Pb* date of 1769 ± 5 Ma, interpreted as the age of gold mineralization. This was followed by two discrete episodes of hydrothermal alteration at 1727 ± 7 Ma and 1673 ± 8 Ma. The three ages are linked to multiple reactivation of the crustal-scale Nanjilgardy Fault during repeated episodes of intracratonic reworking. The regional-scale drivers for Carlin-like gold mineralization at Mount Olympus are related to a change in tectonic regime during the final stages of the intracratonic 1820–1770 Ma Capricorn Orogeny. Our results suggest that substantial sized Carlin-like gold deposits can form in an intracratonic setting during regional-scale crustal reworking. [Display omitted] •Carlin-like gold can form in an intracratonic setting during regional-scale crustal reworking.•LA-ICP-MS pyrite maps from Mount Olympus show geochemical similarities to Carlin-type ores.•Gold mineralization at Mount Olympus occurred at 1769 ± 5 Ma.